The Use of Replacement Models On Determine the Optimal Time to Replacement - ابراهيم سميرة خليل (Journal of Economics and Administrative Sciences, 2013)
Abstract:- The approach maintenance and replacement one of techniques of operations research whom cares of the failure experienced by a lot of production lines which consist of a set of machines and equipment, which in turn exposed to the failure or work stoppages over the lifetime, which requires reducing the working time of these machines or equipment below what can or conuct maintenance process once in a while or a replacement for one part of the machine or replace one of the machines in production lines. In this research is the study of the failure s that occur in some parts of one of the machines for the General Company for Vegetable Oils in 2010 (the failure the failure s that occur during the months of the year), and discuss the possibility of using one of the models replacement in determining time optimization for the replacement process (the month in which the rate total cost less what can be), I have been using a model replacement first and who cares calculate the average total cost of the parts that stop working once in a while (which break down) in 2010 and aimed at increasing the efficiency of the machine or the efficiency of production lines and thus increase production and the lowest possible cost.